Application of talcum powder, trichloroacetic acid and silver nitrate in female rats for non-surgical sterilization: evaluation of the apoptotic pathway mRNA and miRNA genes - Yumrutas, Onder; Kara, Murat; Atilgan, Remzi; Kavak, Salih Burcin; Bozgeyik, Ibrahim; Sapmaz, Ekrem (Wiley, 2015)
There are several methods used for non-surgical sterilization in birth control including quinacrine, trichloroacetic acid (TCA), erythromycin, tetracycline, silver nitrate and talcum powder. Among these, talcum powder, TCA and silver nitrate are the most commonly used. However, the toxic and carcinogenic activities of these chemicals in ovarian tissue have been poorly elucidated. This study demonstrates the expression levels of antioxidant, apoptotic and anti-apoptotic genes after administration of talc powder, TCA and silver nitrate for non-surgical sterilization in female rat models. The expression changes of some microRNAs (miR-15b, miR-21, miR-34a and miR-98) that play key roles in the apoptosis pathway were also included. All expression analyses were evaluated with real-time PCR. The expression levels of all genes appeared to be upregulated in the talcum powder group, but the results were not statistically significant. Increased expression of Gsr and Sod1 genes was statistically significant in the talcum powder group. In TCA and silver nitrate group, expression of all genes was appeared to be elevated but only the Gsr expression was statistically significant in the TCA-administrated group; there were no statistically significant changes in the silver nitrate group. miRNA expression levels were increased in talcum powder and TCA-administrated groups, but these results were not significant. Expression levels of miR-15b, miR-21 and miR-98 in the silver nitrate group were significantly increased. Consequently, these chemicals appear to be non-carcinogenic agents for rat ovarian tissue which do not induce apoptosis. However, talcum powder and TCA can be considered as agents that are toxic to ovarian tissue.
Keywords: antioxidant; apoptosis; miRNA; silver nitrate; talcum powder; trichloroacetic acid